Compatibilized thermoplastic elastomers based on highly filled polyethylene with ground tire rubber. Issue 41 (5th August 2022) - Liu, Shuang; Peng, Zonglin; Zhang, Yong; Rodrigue, Denis; Wang, Shifeng
Abstract: Thermoplastic elastomers (TPE) based on ground tire rubber (GTR) are good strategies for the circular economy and sustainable development of waste tire rubber recycling. However, several parameters must be optimized to produce valuable TPE. The most important ones are GTR concentration and dispersion, as well as crosslinking degree, combined with interfacial interactions between the GTR and the thermoplastic matrix. In this work, TPE based on highly filled linear low‐density polyethylene (LLDPE) with GTR (50%–90%) was prepared via dynamic vulcanization. In particular, different reclaimed GTR (RR) was used alone or with a compatibilizer (maleic anhydride grafted polyethylene, PE‐g‐MAH) to prepare compatibilized TPE. The interactions between the rubber and plastic were quantified by a series of characterizations including mechanical tests, rheological measurements, differential scanning calorimetry, dynamic mechanical analysis and scanning electron microscopy. The results showed that the mechanical properties and processability decreased with increasing GTR content. Although the interfacial compatibility was improved with a higher GTR reclamation degree, the TPE mechanical properties were still gradually decreasing. To improve on these results, PE‐g‐MAH was added to increase the GTR‐LLDPE interfacial interactions. The results showed improvement in terms of mechanical properties and processability, especially for compatibilized TPE based on RR (tensile strength increased from 3.34 to 4.82 MPa and elongation at break from 91% to 101%). Abstract :